2020
DOI: 10.1111/1742-6723.13646
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic outcomes following the introduction of a policy for using soft cervical collars in suspected traumatic cervical spine injury: A retrospective chart review

Abstract: Objective In trauma patients with potential cervical spine injury, immobilisation with a rigid cervical collar is widely recommended to prevent a secondary spinal cord injury. There is a lack of evidence for the effectiveness of this practice, but increasing evidence for complications from rigid collars. Soft foam collars may mitigate some of these issues and are used in our health service in place of rigid collars in selected patients at risk for traumatic cervical spine injury. The objective of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…These survey results are also relevant for the use of selective immobilization protocols. A number of prior studies have documented the discrepancy between assessment findings and treatment provided, most often in the case of not applying devices when indicated [20][21][22]. While past research has noted substantial variation in how providers interpret MOIs, [21] and consequently whom they choose to assess, this area of decision-making has not been prospectively quantified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These survey results are also relevant for the use of selective immobilization protocols. A number of prior studies have documented the discrepancy between assessment findings and treatment provided, most often in the case of not applying devices when indicated [20][21][22]. While past research has noted substantial variation in how providers interpret MOIs, [21] and consequently whom they choose to assess, this area of decision-making has not been prospectively quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the scoring direction of individual questions, its maximum possible score [40] would indicate a high level of skepticism toward the value of treatment (or low level of endorsement), while the minimum [8] would indicate a low level of skepticism (or high level of endorsement). Overall, the median factor score was 26 (IQR: 24-29.75, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Internal consistency of each factor was high (Judging MOIs, 0.77 and Treatment Value, 0.76).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to commend the contribution of Asha et al, who have attempted to address a long-standing knowledge gap with their publication entitled 'Neurologic outcomes following the introduction of a policy for using soft cervical collars in suspected traumatic cervical spine injury: a retrospective chart review'. 1 Spinal immobilisation has been a continual point of conjecture, with current practice dominated by legacy ideologies and perpetual dogma. The routine application of semi-rigid cervical collars has long been a mainstay of contemporary practice, despite no definitive evidence demonstrating its efficacy in preventing secondary spinal cord damage.…”
Section: Editorialmentioning
confidence: 99%
“…Others studies have compared different treatment techniques and found a range of factors and scenarios that influence patient motion apart from the specific device applied, including driving habits, 15,16 extrication, 17 and patient behavior 18,19 . Additional research has examined patient characteristics and outcomes after introducing new guidelines, observing not only substantial undertreatment among patients who met criteria for precautions but also increases in the number of patients with confirmed injuries who received no treatment from emergency medical services (EMS) 20,21 . While a small number of additional studies using high‐level population data have observed no increase in a final diagnosis of spinal cord injury after SMR, 22,23 the prospects of variable practice, ineffective interventions, and patients not receiving the treatment intended for their injury remain a concern.…”
Section: Introductionmentioning
confidence: 99%